Factors Associated with Medication Adherence to Long-Acting Injectable Antipsychotics: Results from the STAR Network Depot Study - Aguglia, Andrea; Fusar-Poli, Laura; Natale, Antimo; Amerio, Andrea; Espa, Irene; Villa, Veronica; Martinotti, Giovanni; Carrà, Giuseppe; Bartoli, Francesco; D’Agostino, Armando; Serafini, Gianluca; Amore, Mario; Aguglia, Eugenio; Ostuzzi, Giovanni; Barbui, Corrado (Pharmacopsychiatry, 2022)
Introduction Long-acting injectable (LAI) antipsychotics are prescribed to people with severe psychiatric disorders who show poor adherence to oral medication. The present paper examined factors potentially associated with medication adherence to LAI treatment.Methods The STAR (Servizi Territoriali Associati per la Ricerca) Network Depot Study was a multicenter, observational, prospective study that enrolled 461 subjects initiating a LAI from 32 Italian centers. After 6 and 12 months of treatment, we evaluated differences between participants with high (≥5 points) and low (<5 points) medication adherence using Kemp’s 7-point scale in sociodemographic, clinical, psychopathological, and drug-related variables. Factors that differed significantly between the two groups were entered for multivariate logistic regression.Results Six months after enrollment, participants with high medication adherence were younger, living with other people, had lower Brief Psychiatric Rating Scale (BPRS) total scores, lower adverse events, and a more positive attitude toward medication than participants with low adherence. Multivariate regression confirmed lower BPRS resistance and activation scores, absence of adverse events, and positive attitude toward medication as factors significantly associated with good adherence. After 12 months, all BPRS subscales were significantly lower in the high adherence group, which also showed a more positive attitude toward medication. BPRS resistance and attitude toward medication were confirmed as factors associated with medication adherence.Discussion Our findings suggest that adherence to LAI is principally related to attitude toward medication and traits of suspiciousness/hostility. Quality of patient-clinician relationship and tailored psychoeducational strategies may positively affect adherence in people undergoing psychopharmacological treatment, including LAI.
Keywords: long-acting injectable; antipsychotics; adherence; schizophrenia; bipolar disorder